A guide to international monetary economics exchange rate theories, systems, and policies (Cheltenham, UK ; Northampton, MA, USA E. Elgar, 2000)
"In this fully revised and updated second edition, Hans Visser includes recent developments in the world economy such as the rise of currency boards and the changing role of the IMF in solving currency crises." "As in the first edition, the emphasis i s on the economic reasoning behind the formulas while introducing students to the mathematics which will enable them to pursue further reading. This book is aimed at advanced students of economics, finance and business as well as professional economists wishing to refresh their knowledge of exchange rate theories."--BOOK JACKET.
Asset models -- Global monetarism -- Monetary models -- Portfolio models -- IS/LM for an open economy -- The basic model -- Macroeconomic policy in a fixed-but-adjustable peg system -- Macroeconomic policy with free-floating exchange rates -- Portfolio analysis and international capital movements -- Overshooting -- Limitations and variants -- Devaluation, the trade balance and the terms of trade -- Dependent-economy models -- The Australian two-sector model -- The balance of payments in a fixed-peg system -- Flexible exchange rates -- Adding a third good -- The long and very long periods -- The long period -- Purchasing power parity -- The very long period -- Exchange rate policy -- Exchange rate system and exchange rate policy -- Current account disequilibria and capital market integration -- Policy coordination -- Payments restrictions -- Payments liberalization -- Monetary unions -- What is a monetary union and what is the use of it? -- Disadvantages of monetary union -- Optimum currency areas -- Potential problems of monetary union -- European monetary union -- Monetary unions in history.
Includes bibliographical references (p. 191-212) and index.
Keywords: Foreign exchange rates; Foreign exchange; Internationale geldmarkt; Internationale monetaire politiek; Wisselkoersen; Internationales Wèahrungssystem.; Wechselkurs; Wechselkurspolitik; Wechselkurstheorie; FOREIGN EXCHANGE RATES; FOREIGN EXCHANGE; Internationale geldmarkt; Internationale monetaire politiek; Wisselkoersen